Risk factors for mechanical complications in very elderly patients with acute myocardial infarction - Yan, Luqin; Yuan, Wei (Frontiers in Medicine, 2025)
BackgroundThe mortality rate for mechanical complications in very elderly acute myocardial infarction (AMI) patients is extremely high, but predictive tools specifically for this population are lacking.MethodsMechanical complications (free-wall rupture, ventricular septal rupture, papillary muscle rupture/dysfunction, ventricular aneurysm) were independently validated. Differences in baseline characteristics, laboratory markers, and outcomes were compared. Missing data underwent sensitivity analysis, with >20% exclusion and <15% imputation. Regression modeling entered variables with univariate association (p < 0.05) or clinical relevance into multivariable logistic regression; final model derived via backward elimination (p < 0.05 retained) with VIF > 5 exclusion. Analyses used SPSS/GraphPad (two-tailed p < 0.05).ResultsThis retrospective cohort study analyzed 2,467 consecutive AMI patients aged ≥ 75 years. Mechanical complications occurred in 9.6% (n = 236) of patients. Ventricular aneurysm (VA) predominated (92.8%), strongly associated with anterior infarcts (71.2%, p < 0.001) and reperfusion (81.7%, p < 0.001). Rupture complications favored non-reperfused infarcts. Patients with mechanical complications exhibited distinct profiles: lower systolic blood pressure (115.9 vs. 123.5 mmHg, p = 0.001), higher STEMI prevalence (60.6% vs. 44.1%, p < 0.001), advanced Killip class III-IV (22.5% vs. 13.3%, p < 0.001), and biomarker evidence of intense inflammation (elevated WBC, neutrophil%, hs-CRP), myocardial injury (higher cTnT, NT-proBNP), and metabolic derangements (hypoalbuminemia, hyperkalemia). Multivariable analysis identified independent predictors: Killip class III/IV (OR = 2.99), elevated neutrophil percentage (OR = 1.05), hyperkalemia (OR = 1.70), and hypoalbuminemia (OR = 0.92). A history of hypertension was paradoxically protective (OR = 0.50).ConclusionThis study identifies ventricular aneurysm as the dominant mechanical complication in very elderly AMI patients, establishes a paradoxical protective role of hypertension history, and proposes a distinct risk profile integrating hemodynamic status, neutrophilic inflammation, and metabolic derangement. These findings are hypothesis-generating and highlight a potentially valuable stratification tool that warrants prospective validation in external cohorts before clinical application.